A Comparative Study of the Theme of Death in the Poems of Gauri Deshpande and Mamta Kalia: Exploring the Theme of Death through the Poetry of Gauri Deshpande and Mamta Kalia (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Modern Indian-English women poets have explored different themes like love, man, Nature, death, God and social issues in their poems. In this paper I have compared the theme of Death in the poems of Gauri Deshpande and Mamta Kalia. Gauri Deshpande presents death in different ways. In one poem, she welcomes death in another poem she presents death as horror. I discuss different views of Gauri Deshpande on a single issue i.e death in her poems. Mamta Kalia is another poet who also explores the theme of death in her poems. She expresses that death should be welcomed with positive note. Gauri Deshpande has connected death with traditional aspects, whereas Mamata Kalai has connected death with material world. The detailed analysis of these two poets about death has been presented in this paper with a comparative note on these two writers.